Novel N-Alkyl 3-(3-Benzyloxyquinoxalin-2-yl) Propanamides as Antiproliferative Agents: Design, Synthesis, In Vitro Testing, and In Silico Mechanistic Study - Samar A. Abubshait (Molecules)
A series of eleven new N-alkyl 3-(3-benzyloxyquinoxalin-2-yl) propanamides were prepared based on the azide coupling of 3-(3-benzyloxyquinoxalin-2-yl) propanhydrazide with a variety of primary and secondary amines and the consequent conjunction of a broad spectrum of lipophile and hydrophile characters to a quinoxaline ring system. 3-(3-benzyloxyquinoxalin-2-yl) propanhydrazide was produced in a two-step reaction of methyl 3-(3-oxo-3,4-dihydroquinoxalin-2-yl) propanoate with benzyl chloride followed by the hydrazinolysis of the corresponding ester. The antiproliferative activity of the compounds was tested in various cancer cell lines, including PC-3, Hela, HCT-116, and MCF-7; they showed a wide spectrum of activity for most of the tested compounds. Compound 6k exhibited the highest activity, which was comparable to that of doxorubicin, with IC50 (µM) values of 12.17 ± 0.9, 9.46 ± 0.7, 10.88 ± 0.8, and 6.93 ± 0.4 µM compared to 8.87 ± 0.6, 5.57 ± 0.4, 5.23 ± 0.3, and 4.17 ± 0.2 µM for doxorubicin against Hela, HCT-116, and MCF-7, respectively. The in silico mechanistic study revealed the inhibition of HDAC-6 through the binding of the unique zinc finger ubiquitin-binding domain (HDAC6 Zf-UBD). The docking results showed a specific binding pattern that emphasized the crucial role of the quinoxaline ring and its substituents. The newly developed derivatives were evaluated for antitumor effects against four cancer cell lines PC-3, HeLa, HCT-116, and MCF-7. This research led to the identification of a quinoxaline-based scaffold exhibiting broad-spectrum antiproliferative activity and a distinct mechanism involving binding to HDAC6 Zf-UBD. The findings highlight its potential for further optimization and preclinical studies to support future anticancer drug development.